Lead and cadmium in infant milk and cereal based formulae marketed in Nigeria: a probabilistic non-carcinogenic human health risk assessment - Zelinjo Nkeiruka Igweze; Osazuwa Clinton Ekhator; Orish Ebere Orisakwe (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. There has been concern on the likelihood of contamination of infant formulae and consequent health risk in children. Objective. This study has assessed and compared the lead and cadmium levels in infant formulae commonly consumed in Nigeria with international regulatory limits. It has also compared the estimated daily intake with Joint FAO/WHO Expert Committee on Food Additives (JECFA) and Proposition 65 Provisional Tolerable Daily Intake. Material and Methods. Lead and cadmium levels in 26 different brands of infant formulae purchased from stores in Port-Harcourt, Rivers state, Nigeria in January 2018 were assayed by Atomic Absorption Spectrophotometry. Results. The lead and cadmium levels in milk based infant formulae ranged from 0.61-3.50 mg/kg and 0.01-0.55 mg/kg respectively whereas the range of the lead and cadmium levels in the cereal and cereal mix based were 0.29-1.95 mg/kg and 0.02-0.37 mg/kg, and 0.47-2.34 mg/kg and 0.001-0.46 mg/kg respectively. The mean lead level in the milk-based formulae (1.49 0.89 mg/kg) was slightly higher than other groups of formulae but the difference was not significant (p<0.05). The mean level of cadmium (0.17 mg/kg) in milk-based infant formulae was higher than levels in cereal and cereal mix but there was no significant statistical difference (p<0.05) between the samples. The lead and cadmium level in milk, cereal and cereal mixed based infant formulae were above the food safe limits. Conclusions. The consumption of infant formulae may add to the body burden of cadmium and lead of children with attendant public health implication. Regular monitoring and safety assessment of metals contamination of these infant formulae is advised.